Resolving pertussis immunity and vaccine effectiveness using incidence time series - Lavine, Jennie S (2012)
Resolving the long-term, population-level consequence of vaccine-induced immunity to pertussis is a key challenge for control strategies and vaccine development. Controlled vaccine efficacy studies provide invaluable information; however, they are limited in scope by their sample size and follow-up duration. Long-term time series of incidence data collected by public health institutions provide insight at a broader scale, especially when the data are spatially explicit and age stratified. By using modern ecological and statistical methodolgies, which are reviewed in this paper, new insights into the duration of transmission-blocking immunity and the age-specific patterns of transmission can be gained. Recent advances in computing power and statistical software development will increasingly make these methods available to public health practitioners, vaccine developers and academics alike.